Bilateral pulvinar responsive neurostimulation for bilateral multifocal posteriorly dominant drug resistant epilepsy - Richard Wang; Ariel Sacknovitz; Sima Vazquez; Jose Dominguez; Patty McGoldrick; Steven Wolf; Vishad Sukul; Carrie Muh; Sanjay E. Patra; David E. Burdette (Epilepsia Open)
Abstract Objective To describe four cases of Responsive Neurostimulation (RNS) in the bilateral pulvinar nuclei (PUL) in individuals with drug resistant epilepsy (DRE). This will show that due to widespread PUL connectivity, bilateral PUL RNS may be an option for some individuals with bilateral multifocal epilepsy. Methods This study comprises two centers' experience with bilateral PUL RNS for DRE. Patients treated with bilateral PUL RNS at Westchester Medical Center (Valhalla, NY) and Corewell Health (Grand Rapids, MI) between the years 2019 and 2022 were analyzed and described. Presented here are methods for target selection, device programming, and clinical outcomes. Results Two patients with Lennox–Gastaut phenotype (aged 13 and 21 years) with posteriorly dominant discharges were implanted with bilateral PUL electrodes. Additionally, two patients (aged 20 and 31 years) with independent left and right occipital bilateral multifocal seizure onsets were implanted with bilateral RNS devices targeting the ipsilateral PUL and ipsilateral occipital cortex. Subclinical and clinical seizures were captured by RNS electrocorticography (ECoG) in all patients. RNS implantation and treatment was well‐tolerated without adverse effects in all patients. Relative to baseline, two patients had 25% and 50% reduction in disabling seizures, and two patients had 71% and 100% reduction in disabling seizures. Stimulation paradigms utilized high frequency stimulation in both Lennox–Gastaut phenotype patients. Low frequency (individualized to the terminal ictal frequencies) stimulation was effective in the two bioccipital patients. Significance RNS with electrode placement targeting bilateral PUL is safe, and no adverse effects have been attributable to the pulvinar electrode placement. PUL responsive neurostimulation is potentially effective for patients with bilateral multifocal, posteriorly dominant DRE. Both high and low frequency responsive stimulation are treatment options. Longer follow‐up will shed light on the ultimate reduction of seizure burden. Plain Language Summary We describe four cases where stimulation devices were placed in the Pulvinar area of the thalamus (central sensory area in the brain). This is very unique and different location than where these devices are typically placed. These patients all had great outcomes with marked seizure reduction, demonstrating that this placement is both safe and effective.